2015
DOI: 10.3329/uhj.v10i1.24598
|View full text |Cite
|
Sign up to set email alerts
|

Marfan’s Syndrome with Dissecting Aortic Aneurysm - A Case Report

Abstract: Marfan’s Syndrome patients with aortic root aneurysm or dissection may present with shortness of breath and chest pain and may be missed during clinical evaluation. Subsequently, sudden aortic rupture may occur in these groups of patients and give rise to fatal outcome. Increasing awareness of Marfanoid signs amongst clinicians are important for early diagnosis and treatment of dissecting aortic aneurysm. Marfan’s Syndrome with dissecting aortic aneurysm should not be overlooked among patients with shortness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Other reports include Patau syndrome [ 53 ], Turner syndrome [ 54 , 55 ], intersex disorders (absence of typical binary notions of male or female bodies, e.g., due to aneuploidy) [ 56 , 57 ], and Klinefelter syndrome [ 55 , 58 , 59 ]. Among rare conditions, previous research reported several cases of Marfan syndrome [ 60 ], scleroderma [ 61 , 62 ], multiple epiphyseal dysplasia [ 63 ], Cutis laxa [ 64 ], and Bart’s syndrome [ 65 ].…”
Section: Epidemiology Of Genetic Diseases In Bangladeshmentioning
confidence: 99%
“…Other reports include Patau syndrome [ 53 ], Turner syndrome [ 54 , 55 ], intersex disorders (absence of typical binary notions of male or female bodies, e.g., due to aneuploidy) [ 56 , 57 ], and Klinefelter syndrome [ 55 , 58 , 59 ]. Among rare conditions, previous research reported several cases of Marfan syndrome [ 60 ], scleroderma [ 61 , 62 ], multiple epiphyseal dysplasia [ 63 ], Cutis laxa [ 64 ], and Bart’s syndrome [ 65 ].…”
Section: Epidemiology Of Genetic Diseases In Bangladeshmentioning
confidence: 99%